2013
DOI: 10.1186/1471-2458-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Burden of childhood diseases and malnutrition in a semi-urban slum in southern India

Abstract: BackgroundIndia has seen rapid unorganized urbanization in the past few decades. However, the burden of childhood diseases and malnutrition in such populations is difficult to quantify. The morbidity experience of children living in semi-urban slums of a southern Indian city is described.MethodsA total of 176 children were recruited pre-weaning from four geographically adjacent, semi-urban slums located in the western outskirts of Vellore, Tamil Nadu for a study on water safety and enteric infections and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 36 publications
6
47
1
3
Order By: Relevance
“…A nested case-control study was conducted among children residing in a slum community in the western outskirts of Vellore, Tamil Nadu, India, using data from two community-based studies on childhood cryptosporidiosis between 2008 and 2013. The first study was a quasi-experimental study on the effect of protected drinking water supply (bottled drinking water) in preventing childhood cryptosporidiosis, where 176 children were recruited at birth or during exclusive breastfeeding and followed weekly until 2 years of age 33 ; drinking bottled water did not confer additional protection against cryptosporidial infections. 34 The second study was a birth-cohort study on immune responses to Cryptosporidium spp.…”
Section: Methodsmentioning
confidence: 99%
“…A nested case-control study was conducted among children residing in a slum community in the western outskirts of Vellore, Tamil Nadu, India, using data from two community-based studies on childhood cryptosporidiosis between 2008 and 2013. The first study was a quasi-experimental study on the effect of protected drinking water supply (bottled drinking water) in preventing childhood cryptosporidiosis, where 176 children were recruited at birth or during exclusive breastfeeding and followed weekly until 2 years of age 33 ; drinking bottled water did not confer additional protection against cryptosporidial infections. 34 The second study was a birth-cohort study on immune responses to Cryptosporidium spp.…”
Section: Methodsmentioning
confidence: 99%
“…Although India has succeeded in reducing child mortality to a considerable extent [Gupta et al 2009], a considerable number of children are still dying of these two diseases because of piecemeal approach to service provision and those at greatest risk are not being identified and reached [WHO/UNICEF 2013]. Identifying those at greatest risk, hardest to reach and most neglected, and targeting them with effective interventions will help to close the gap, eventually Many studies in India and abroad have already studied prevalence and determinants of diarrhoea [Sarkar et al 2013;Khan et al 2013; Luke and McPike 2012; Gladstone 2010; Jadhav 2009;Sakdapolrak et al 2011; Melo et al 2008] and ARI [Islam 2013;Srivastava et al 2012; Wadgave and Godale 2011; Prajapati 2011;Prietsch 2008;Savitha 2007; Gupta et al 2007;Acharya 2003;Broor 2001;Biswas 1999]. However, the scope of most of the previous studies is geographically restricted.…”
mentioning
confidence: 99%
“…It also showed an occurrence of 7.5 episodes of ARI/child year and another interesting finding was that 98% of the ARIs were actually URTIs. 19 Several 'small scale' community based studies over the years have reported that poor socio-economic factors; low level of literacy, suboptimal breast feeding malnutrition, unsatisfactory level of immunization coverage, cooking fuel used other than liquefied petroleum gas as risk factors contributing to increased burden of ARI among children. [20][21][22] Identification of severe respiratory infections by health care workers from rural area, wide access to antibiotics and its administration by health care workers was seen as successful model by Gadchiroli project management of childhood illness by holistic approach of Integrated management of neonatal and childhood illnesses (IMNCI).…”
Section: Discussionmentioning
confidence: 99%